Formation and forms of organization of ecological audit on agricultural enterprises - Кузьменко, О. К. (Scientific Progress & Innovations, 2013)
Formation of ecological audit in Ukraine and forms of organization of ecological audit on the agricultural enterprises of the country is considered. Objects and subjects of environmental audit are defined. The analysis of basic factors and stages of forming of ecological audit is conducted on agricultural enterprises. The chart of organization of ecological audit on agricultural enterprises is offered.